Seismocardiography as a tool for assessment of bi-ventricular pacing. (28th October 2022) - Sørensen, Kasper; Søgaard, Peter; Emerek, Kasper; Schou Jensen, Ask; Struijk, Johannes Jan; Schmidt, Samuel Emil
Abstract: Objective. Conduction-induced heart failure in patients with left bundle branch block (LBBB) can benefit from cardiac resynchronization therapy (CRT). However, some patients are non-responders to the therapy with one contributing factor being poor optimization of the atrioventricular (AV) pacing delay. In this study, we have investigated the pacing-induced changes in the seismocardiogram (SCG). Approach. 14 patients with heart failure, LBBB, and CRT were included. SCG was recorded with pacing turned on and off. Based on a mean SCG heartbeat from each patient, fiducial points were annotated, and cardiac timing intervals (CTI) and amplitudes were derived. These were compared between the CRT group and a group of healthy normal subjects ( n = 14). Echocardiography was also used to derive CTI. Intervals derived from the SCG and echocardiogram were correlated. Main results. The isovolumetric contraction time (IVCT) derived from SCG was significantly shorter in the CRT group when the pacemaker was turned on (63.2–52.6 ms, p = 0.027). The first peak-to-peak amplitude in the systolic complex was significantly larger with the pacemaker turned on ( p = 0.002), as well as the ∣max-min∣ amplitude in the systolic complex ( p = 0.003). Isovolumetric relaxation time and left ventricular ejection time (LVET) were not significantly different between pacemaker settings. Compared to normal subjects, IVCT was significantly prolonged with the pacemaker turned off. All amplitudes were significantly larger in the healthy subject group. IVCT and LVET derived from SCG were significantly correlated to the echocardiogram. Significance. IVCT shortened and SCG amplitudes increased in response to CRT, indicating a more efficient ventricular contraction. This demonstrates the possibility to detect cardio-mechanic changes in response to treatment with the SCG. However, for the patients the systolic part of the SCG was abnormal and difficult to characterize, raising concerns about the correct interpretation of the SCG.